Effects of Inertia and Viscosity on Single Droplet Deformation in Confined Shear Flow (Communications in Computational Physics, 2020)
Lattice Boltzmann simulations based on the Cahn-Hilliard diffuse interfaceapproach are performed for droplet dynamics in viscous fluid under shear flow, wherethe degree of confinement between two parallel walls can play an important role. Theeffects of viscosity ratio, capillary number, Reynolds number, and confinement ratioon droplet deformation and break-up in moderately and highly confined shear flowsare investigated.